Islamic Education through the Digital Storytelling Method in Islamic Date Learning: (Classical Narrative Revitalization Study for the Millennial Generation) - Ardani; Prospery Mwansa Mwila (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2025)
This study aims to examine how the digital storytelling method can be used as a means of revitalizing classical narratives in learning Islamic tarikh for the millennial generation. Using a qualitative research approach based on library research, this study analyzes various academic literature and relevant classical and contemporary Islamic scholarly sources. The results show that digital storytelling can be an effective pedagogical medium to convey Islamic history in a contextual, interesting and meaningful way. The transformation of classical narratives into digital formats-such as animated videos, podcasts, and interactive infographics-increases learners' absorption, interest in learning, and emotional engagement. In addition, this method is in line with the visual, fast-paced and technology-based learning characteristics of the millennial generation. In the context of Islamic education, digital storytelling not only functions as a medium for delivering material, but also as a means of character building, value internalization, and strengthening students' Islamic identity. This study concludes that digital storytelling has great potential in recontextualizing Islamic history and becoming an epistemological bridge between classical scientific traditions and the challenges of the digital world. Therefore, the integration of this method in the Islamic tarikh curriculum is an important strategy in responding to today's pedagogical needs. Keywords: Tarikh Islam, Digital Storytelling, Classical Narratives, Islamic Education, Millennial Generation, Digital Media, Contextual Learning